2013
DOI: 10.1089/apc.2013.0110
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Antiretroviral Therapy in Youth with HIV: A U.S.-Based Provider Survey

Abstract: In 2009, the Department of Health and Human Services (DHHS) recommended initiating antiretroviral therapy (ART) for youth with HIV at higher CD4 counts ( £ 500 cells/mm 3 ) than previously recommended ( £ 350 cells/mm 3 ). Barriers experienced by providers regarding ART initiation in this population have not been assessed. From 12/ 2011-01/2012, we asked providers from the HIV Medicine Association listserv who prescribed ART to youth (ages 13-25 years) with behaviorally-acquired HIV to complete a web-based sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…31,32 Given the risks of resistance mutations associated with ART nonadherence 4243 , providers may opt to delay ART until they identify appropriate “treatment readiness” among patients. This potential provider bias or concern of not wanting to prescribe ART to youth they deem potentially non-adherent or less “responsible” and rigorous in their health care behaviors and scheduling demands of ART is partially supported by the findings that consistent appointment keeping, lack of symptomatic substance use, older age, employment, and higher levels of educational attainment were significantly related to ART use among both BIY and PIY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Given the risks of resistance mutations associated with ART nonadherence 4243 , providers may opt to delay ART until they identify appropriate “treatment readiness” among patients. This potential provider bias or concern of not wanting to prescribe ART to youth they deem potentially non-adherent or less “responsible” and rigorous in their health care behaviors and scheduling demands of ART is partially supported by the findings that consistent appointment keeping, lack of symptomatic substance use, older age, employment, and higher levels of educational attainment were significantly related to ART use among both BIY and PIY.…”
Section: Discussionmentioning
confidence: 99%
“…2630 Some patient characteristics, such as substance use and unstable housing, may elicit concerns among providers about patients’ treatment readiness and may be perceived as significant barriers to initiating youth on ART, despite the landmark results of HPTN 052 and effects of early ART initiation on decreasing HIV infectivity and reducing the likelihood of HIV transmission. 15, 3133 Finally, perinatally infected youth (PIY) face additional challenges such as HIV treatment fatigue due to use of ART since birth as well as accumulation of resistance mutations resulting in limited ART options. 3334 Thus, factors influencing access, utilization of and response to HIV treatment as well as engagement and retention in care may differ between PIY and BIY who acquired HIV infection as adolescents or young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Their physicians must be willing to accept potential barriers (erratic lifestyle, substance abuse, unstable housing, and nondisclosure) to initiating youth on life-long ART. 46 Once in care, patients must remain in care and maintain a high degree of adherence to ART. Despite this, patients may experience baseline viral resistance or could develop resistance due to poor adherence, drug-drug interactions, medication side effects, malabsorption of medication, or any other factor that can cause prolonged low serum blood levels of ART.…”
Section: Antiretroviral Therapy and Resistancementioning
confidence: 99%
“…Gargliado et al in a survey of US providers from the American Academy of HIV Medicine also found unstable housing and drug use were perceived providers as large barriers to ART initiation. 32 Lastly, there are almost no data on facility-level barriers to ART initiation or time to ART initiation. In this analysis, we did not find any association between time to ART initiation and facility characteristics (facility patient volume, Ryan White HIV/AIDS Program funding status, and university affiliation).…”
Section: Discussionmentioning
confidence: 99%